Dari Sitoluama untuk Indonesia : Menumbuhkan Generasi Ilmuwan Melalui DMSC 2024 - Regina Ayunita Tarigan; Asido Saragih; Junita Amalia; Jaya Santoso; Ana Muliyana; Sari Muthia Sari; Andrew Rolas Siagian (Pusat Riset dan Inovasi Nasional, 2025)
The proficiency of Indonesian students in mathematics and science remains relatively low, as reflected in the 2022 PISA survey, which ranked Indonesia 69th out of 81 participating countries. This low level of mathematical and scientific literacy has become a major concern in efforts to improve the quality of education. This community service activity aims to foster interest and motivation among senior high school students (SMA/SMK/MA or equivalent) in the fields of mathematics, physics, chemistry, and biology through the organization of the Del Mathematics and Science Competition (DMSC) in 2024. The competition was conducted in two stages: an online preliminary round on November 2, 2024, and an on-site final round on November 9, 2024, at Institut Teknologi Del, coinciding with World Scientiest Day. The implementation method included competition promotion, online participant selection, and in-person contest execution with an objective scoring system. The findings indicated high enthusiasm among participants from various regions of Indonesia, along with improved understanding and confidence in solving concept-based problems. The implications of this activity suggest that science-based competitions can serve as effective platforms to raise public awareness of the importance of mastering science and support national efforts to enhance the quality of education in mathematics and science